Spatial Variability of Soil Properties around Baturiya Sanctuary, Jigawa State, Nigeria - Danjuma, Muhammad Nuraddeen; Mustapha Zakariya; Mohammed Ahmed; Sa'adu Abubakar Mafara (Journal of Techno-Social, 2020)
Soil properties intricately vary spatially owing to several natural and anthropogenic factors including parent material, terrain as well as land use. The aim of this study is to assess the spatial variability of soil samples collected from three different land use types namely: reserved area, parkland and farmland around Baturiya Sanctuary, northwestern Nigeria with a view to providing information that will assist the government in planning and conservation of the area. Free traverse sampling technique was used to collect soil samples at the depth of 0-30cm. Laboratory analysis was done for the following parameters: bulk density, PSD, phosphorous, pH, EC, total nitrogen, exchangeable bases (Mg, Na, and K), and CEC. Geostatistical technique (semivariogram analysis) was used to test variation in soil properties. Result of the study depicted that It also indicated that BD (1.24 g/cm3), clay (22%), total nitrogen (0.25 g/kg), available phosphorous (32.61 mg/g), OC (1.6%) and Mg (0.05) are highest in reserved area. Also sand (55%) and silt (29%), pH (5.0), EC (522), Na (0.007), K (0.44) and CEC (4.5meq/100g) are highest in farmland. The variogram based nugget-sill ratio showed strong dependency with 0 (N, EC, OC) and weak dependency 1 (BD, Na) on the scale of 0.25 high, 0.25 – 0.75 moderate and 0.75 weak. In conclusion, this study found that soil properties in area showed high to moderate spatial dependency except for BD, Mg, K, and Na which showed low spatial autocorrelation owing increasing human activities in the area. This study depicted that apparently limitation by few samples have influenced the pattern in the result otherwise spatial variability of certain elements may be more discernible and beyond reasons such land use and parent materials.